Factors Associated with Hypertension in Pregnant Women at Sukarejo Village, Tanjung Jabung Barat District - Adelina Fitri; Ajeng Tri Yani Safitri; M. Ridwan; Hubaybah; Fitria Eka Putri; Ashar Nuzulul Putra (International Journal of Health Engineering and Technology, 2022)
Hypertension in pregnant women is a factor in the occurrence of illness and death in the mothers or fetus. The causes of hypertension during pregnancy are influenced by various factors including maternal age, family history of hypertension, obesity, physical activity and parity. The purpose of this study was to analyze the factors associated with hypertension in pregnant women at Sukarejo Public Health Center, Tanjung Jabung Barat District. The design of the research was Cross Sectional. The population was all pregnant women in Sukarejo Village, Tanjab Barat Regency with a sample of 71 pregnant women (total sampling). The independent variables are maternal age, maternal occupation, parity, family history of hypertension, food consumption patterns and physical activity. Data collection was carried out by interview using questionnaires and measurements. The data obtained were analyzed by univariate and bivariate analysis using the Chi Square test. The proportion of hypertension in pregnant women is 54.9%. The proportion of mothers who had a family history of hypertension among pregnant women with hypertension was 86.2%, the proportion of poor food consumption patterns among pregnant women with hypertension was 69.7% and the proportion of active mothers in pregnant women with hypertension was 87.5%. Statistical analysis showed a relationship between family history of hypertension (p = 0.000, PR = 2.58), diet (p = 0.036, PR = 1.65) and physical activity (p = 0.000, PR = 0.43) with hypertension in pregnant women. The dominant cause of hypertension in pregnant women is a family history of hypertension. Pregnant women need to always check blood pressure and pregnancy checks so that they can detect early signs of hypertension.